2019
DOI: 10.1103/physreva.100.013406
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term gain dynamics in N2+ air lasing

Abstract: Air lasing in the nitrogen molecular ion is not well understood because the complex physics responsible for gain is interwoven with pulse propagation in an extreme environment. Here we use a short gas jet to limit the interaction length, thereby removing the propagation effects. We report on several mechanisms that contribute to the decay of gain in different conditions, and experimentally isolate two decay timescales: the decay of long-term gain due to collisional state mixing, and short-term gain that cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…For clarity, we refer to the additional pulse as "control." This experiment minimizes the interaction length using a narrow gas jet in vacuum to isolate gain from the effects of propagation [18,19]. By vary-ing both control and probe delays, we also observe modified gain and emission.…”
Section: Introductionmentioning
confidence: 89%
“…For clarity, we refer to the additional pulse as "control." This experiment minimizes the interaction length using a narrow gas jet in vacuum to isolate gain from the effects of propagation [18,19]. By vary-ing both control and probe delays, we also observe modified gain and emission.…”
Section: Introductionmentioning
confidence: 89%
“…For increasing pump intensity, the oscillating gain starts to occur for virtually all pump-probe time delays as observed in the nitrogen gas jet experiments in Ref. [39].…”
Section: Resultsmentioning
confidence: 56%
“…Taking into account the effects of gain narrowing and inelastic collisions that destroy the rotational coherences in the ionic states, our results reproduce the typical observations made in pumpprobe "air lasing" experiments (see e.g., Refs. [14,21,38,39]): a rapid increase of the gain as a function of the pump-probe delay during the first few hundreds of femtoseconds, followed by a slow decay of the gain for delays up to tens of picoseconds that is periodically modulated by the molecular alignment dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, under similar experimental conditions, the optical gain was found to last for less than 10 ps [26,27], in an obvious contradiction with the earlier results. Recently, Britton and co-workers performed the gain dynamics measurement for gas cell and gas jet [28]. They reported that the decay process of the gain depends sensitively on the concentration of the N 2 .…”
Section: Introductionmentioning
confidence: 99%